2021
DOI: 10.3126/bjhs.v6i2.40354
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Body Mass Index and Blood Pressure Among Medical Students of Tertiary Care Teaching Hospital in Birgunj

Abstract: Introduction: Body mass index is an important parameter associated with a variety of disease processes. The risk of hypertension and cardiovascular diseases increases with an increase in body mass index. The study was conducted to compare the relationship between body mass index and blood pressure. Objective: To evaluate the prevalence and correlate the Obesity and Hypertension in    medical students  Methodology: The study was conducted in 200 students (113 males and 87 females). Height, weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Underweight subjects were less likely to have high BP than healthy subjects with normal BMI. Our findings were similar to a study done by Esha Shrestha et al where BMI was a strong predictor of hypertension13 . Humayun et al found BMI is more associated HTN compared to age14 .…”
supporting
confidence: 93%
“…Underweight subjects were less likely to have high BP than healthy subjects with normal BMI. Our findings were similar to a study done by Esha Shrestha et al where BMI was a strong predictor of hypertension13 . Humayun et al found BMI is more associated HTN compared to age14 .…”
supporting
confidence: 93%
“…The prevailing circumstances in the country could potentially be linked to a deficiency in students' comprehension of pharmacovigilance and the reporting of adverse drug reactions (ADRs). The educational curriculum and training programs in Nepal may not be adequately equipped to address these complexities, leading to students grappling with the intricacies of pharmacovigilance and ADR reporting (12).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies [26,33,34,43] reported mean DMFT or DFR in patients with periodontitis. One study [37] indicated significant positive associations between the periodontal disease severity (CDC-AAP) [23] and the amount of decayed, missing and filled teeth surfaces (DMFS) (OR adjusted = 1.03, 95% CI: 1.01-1.05) and the decayed surfaces (DS) indices (OR adjusted = 1.18, 95% CI: 1.05-1.32) as well as between the percentage of sites with CAL ≥ 3 mm and DMFS (OR adjusted = 1.03, 95% CI: 1.00-1.05) and DS indices (OR adjusted = 1.12, 95% CI: 1.00-1.25).…”
Section: Mean Dmft or Dfrmentioning
confidence: 99%